Analisis self-regulated learning (SRL) siswa kelas V di SDN 2 Kadudampit - Imam Subekhi, Andri; Kusmana, Nandang; Indah Pratiwi, Rosi; Rianti, Rima; Selviana, Anisa; Asmariah, Siti (Metakognisi, 2023)
SRL is important for fifth grade students because it becomes a consideration in the learning and teaching process, especially fifth grade students who are faced with the challenges of the next school level. This study aims to analyze the self-regulated learning (SRL) of the fifth grade students of SDN 2 Kadudampit. This study uses a qualitative descriptive approach with a survey method that describes a phenomenon in a particular area. The number of samples used was 33 students of class V. The instrument used was the SRL questionnaire with a Likert scale of 1-5 with alternative gradations of answers strongly agree-strongly disagree. The analysis used is descriptive qualitative analysis. The results of the study show that in general, the SRL ability of class V SDN 2 Kadudampit is in the high category. However, if it is translated based on the indicators, the SRL on the cognitive and self-reflection indicators is indeed in the high category, but the performance indicator shows the medium category. Therefore, efforts are needed from teachers, schools, parents, and students to be able to improve performance in learning through the application of learning models, learning media, parental and teacher guidance, and school policies that support the creation of a positive learning climate.